Generalized pinning synchronization of delayed Cohen–Grossberg neural networks with discontinuous activations. (August 2018) - Wang, Dongshu; Huang, Lihong; Tang, Longkun; Zhuang, Jinsen
Abstract: In this article, generalized pinning synchronization problem is investigated for a class of Cohen–Grossberg neural networks with discontinuous neuron activations and mixed delays. By designing generalized pinning state-feedback and adaptive controllers, several criteria for global exponential synchronization and global asymptotical synchronization of the drive–response based system are obtained in view of non-smooth analysis theory with generalized Lyapunov functional method, in which first pinning the neurons with very small self-inhibition and small amplification functions is pointed out. Some numerical examples are given to illustrate the feasibility of the obtained results.